Collective bargaining and industrial disputes in Ireland - McAuley, D. J. (Statistical and Social Inquiry Society of Ireland, 1967)
This paper falls into three main sections. The first section contains a general description of the legislative and institutional framework of the industrial relations system. The second section concerns collective bargaining between employers and trade unions, conciliation procedures and the incidence of industrial conflict in recent years. In the final section a number of different aspects of industrial relations are discussed including wage bargaining techniques, incomes policy and dispute situations which can be related to the existing institutional arrangements. Where appropriate references are made to practices and procedures in industrial relations in other countries.
Read before the Society, 14 April 1967
Keywords: Collective bargaining in Ireland; Industrial disputes in Ireland; Trade unions in Ireland; 314.15